2015
DOI: 10.1371/journal.pone.0134837
|View full text |Cite
|
Sign up to set email alerts
|

Assembly and Analysis of Differential Transcriptome Responses of Hevea brasiliensis on Interaction with Microcyclus ulei

Abstract: Natural rubber (Hevea brasiliensis) is a tropical tree used commercially for the production of latex, from which 40,000 products are generated. The fungus Microcyclus ulei infects this tree, causing South American leaf blight (SALB) disease. This disease causes developmental delays and significant crop losses, thereby decreasing the production of latex. Currently several groups are working on obtaining clones of rubber tree with durable resistance to SALB through the use of extensive molecular biology techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…These reads can be aligned to a reference genome when available or assembled de novo without the genomic reference to produce a genome-scale transcription map comprising both the transcriptional profile and/or level of expression for each gene (Wang, Gerstein, & Snyder, 2009). Transcriptome sequencing by RNA-Seq provides fundamental information for gene discovery and quantification of gene expression (Huynh, Page, Richardson, & Udall, 2015;Kim et al, 2014), comparative genomic studies (Bindschedler, Panstruga, & Spanu, 2016;Páez, Romero, Restrepo, Gutiérrez, & Castaño, 2015;Wang, Shi, & Rinehart, 2015), secretome analysis and prediction of fungal candidate effectors (Bruce et al, 2014;Guyon, Balagué, Roby, & Raffaele, 2014;Liu et al, 2015;Meinhardt et al, 2014). Whole-genome sequencing and assembly for powdery mildew pathogens are hampered by the obligate nature of the pathogen and by large numbers of repetitive elements throughout the genomes (Spanu et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These reads can be aligned to a reference genome when available or assembled de novo without the genomic reference to produce a genome-scale transcription map comprising both the transcriptional profile and/or level of expression for each gene (Wang, Gerstein, & Snyder, 2009). Transcriptome sequencing by RNA-Seq provides fundamental information for gene discovery and quantification of gene expression (Huynh, Page, Richardson, & Udall, 2015;Kim et al, 2014), comparative genomic studies (Bindschedler, Panstruga, & Spanu, 2016;Páez, Romero, Restrepo, Gutiérrez, & Castaño, 2015;Wang, Shi, & Rinehart, 2015), secretome analysis and prediction of fungal candidate effectors (Bruce et al, 2014;Guyon, Balagué, Roby, & Raffaele, 2014;Liu et al, 2015;Meinhardt et al, 2014). Whole-genome sequencing and assembly for powdery mildew pathogens are hampered by the obligate nature of the pathogen and by large numbers of repetitive elements throughout the genomes (Spanu et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Whole-genome sequencing and assembly for powdery mildew pathogens are hampered by the obligate nature of the pathogen and by large numbers of repetitive elements throughout the genomes (Spanu et al, 2010). Transcriptome sequencing by RNA-Seq provides fundamental information for gene discovery and quantification of gene expression (Huynh, Page, Richardson, & Udall, 2015;Kim et al, 2014), comparative genomic studies (Bindschedler, Panstruga, & Spanu, 2016;Páez, Romero, Restrepo, Gutiérrez, & Castaño, 2015;Wang, Shi, & Rinehart, 2015), secretome analysis and prediction of fungal candidate effectors (Bruce et al, 2014;Guyon, Balagué, Roby, & Raffaele, 2014;Liu et al, 2015;Meinhardt et al, 2014). Thus, the aim of our study was to develop genomic resources, through transcriptome profiling of epiphytic hyphae/conidia and haustoria and identification of potential microsatellites for population genetic studies of P. pannosa, infecting an economically important tree crop Eucalyptus urophylla.…”
Section: Introductionmentioning
confidence: 99%
“…The first draft Hevea genome was released by a Malaysian team 7 that was participant to the recent boom in transcriptomic and proteomic studies of the species [8][9][10][11] . However, its low sequence coverage (∼13×) and a lack of large insert libraries (such as fosmid-or BAC-based clone libraries) have limited the success of genome assembly (a scaffold N50 size of 2,972 bp), precluding its application for furthering quality research in the field.…”
mentioning
confidence: 99%
“…Different initiatives have associated GWAS results with RNA-Seq data (Yan et al, 2020), linking causal genes relevant to the observed phenotypic variation with cell transcription activity profiles (Schaefer et al, 2018; Nguyen et al, 2019). In Hevea, however, RNA-Seq-based studies have been mainly performed to investigate differentially expressed genes (DEGs) under different environmental or stress conditions and profiling rubber tree samples (Hurtado Páez et al, 2015; Sathik et al, 2018; Mantello et al, 2019; Ding et al, 2020; Ding et al, 2020). Although the integration of GWAS with RNA-Seq methodologies has proven to provide a deeper comprehension of the genetic relationships involved in trait definition, there is no study, to date, aggregating such data in Hevea.…”
Section: Introductionmentioning
confidence: 99%